2022
DOI: 10.3389/fimmu.2022.864423
|View full text |Cite
|
Sign up to set email alerts
|

A Toolkit for Profiling the Immune Landscape of Pediatric Central Nervous System Malignancies

Abstract: The prognosis of pediatric central nervous system (CNS) malignancies remains dismal due to limited treatment options, resulting in high mortality rates and long-term morbidities. Immunotherapies, including checkpoint inhibition, cancer vaccines, engineered T cell therapies, and oncolytic viruses, have promising results in some hematological and solid malignancies, and are being investigated in clinical trials for various high-grade CNS malignancies. However, the role of the tumor immune microenvironment (TIME)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 169 publications
(193 reference statements)
0
4
0
Order By: Relevance
“…Even though microglia are the most dominant immune cells in the brain (80%), other immune cell types have been identified in the brain including B cells, dendritic cells, macrophages, monocytes, myeloid cells, natural killer (NK) cells, and T cells [ 12 , 36 38 ]. Nevertheless, the limited number of tumor-infiltrating immune cells compared to the high density of tumor cells can limit the sensitivity of bulk techniques [ 39 ]. The estimation of immune cell types in the samples by NanoString and RNA sequencing shows mostly incomparable results (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Even though microglia are the most dominant immune cells in the brain (80%), other immune cell types have been identified in the brain including B cells, dendritic cells, macrophages, monocytes, myeloid cells, natural killer (NK) cells, and T cells [ 12 , 36 38 ]. Nevertheless, the limited number of tumor-infiltrating immune cells compared to the high density of tumor cells can limit the sensitivity of bulk techniques [ 39 ]. The estimation of immune cell types in the samples by NanoString and RNA sequencing shows mostly incomparable results (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of immune cell infiltration in pediatric gliomas demonstrated that myeloid cells are major components of the TME and show enrichment of CD8+ T cells and CD45+ leukocytes in low-grade gliomas compared to high-grade gliomas [ 77 ]. While the percentage of tumor-associated CD68+ macrophages is comparable across subgroups, diffuse midline gliomas have the lowest number of infiltrating CD8+ T cells and CD163+ macrophages, which contributes to their immunosuppressive phenotype [ 78 ].…”
Section: Tme Immune Profiling In Pediatric Solid Tumorsmentioning
confidence: 99%
“…In pediatric patients, ependymomas comprise ~10% of primary central nervous system tumors, with the majority arising in the posterior fossa [ 96 ]. Pediatric ependymomas with higher infiltration of CD3+ and CD8+ T cells in the microenvironment at diagnosis had a longer progression-free survival, while elevated Forkhead box P3 regulatory T cells and CD68+ macrophages were correlated with a shorter survival rate [ 78 ].…”
Section: Tme Immune Profiling In Pediatric Solid Tumorsmentioning
confidence: 99%
See 1 more Smart Citation